NMR Spectroscopy: A Useful Tool in the Determination of the Electrophilic Character of Benzofuroxans - Case Examples of the Reactions of Nitrobenzofuroxans with Dienes and Nucleophiles - Sebban, M.; Sepulcri, P.; Jovene, C.; Vichard, D.; Terrier, F.; Goumont, R. (IntechOpen, 2012)
None